2021
DOI: 10.1136/jclinpath-2021-207952
|View full text |Cite
|
Sign up to set email alerts
|

BAP1-deficient meningioma presenting with trabecular architecture and cytokeratin expression: a report of two cases and review of the literature

Abstract: AimsBRCA (BReast CAncer gene)-associated protein 1 (BAP1), encoded by the BAP1 gene, a tumour suppressor that is lost in several cancers. Importantly, such mutations have been shown to be susceptible to poly (ADP-ribose) polymerase (PARP) inhibition in preclinical studies, offering hope for targeted therapy. While rare, BAP1 loss has been observed in a subset of rhabdoid and papillary meningioma and is associated with earlier recurrence. We seek to add to the literature on this rare disease and advocate for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Of note, our NGS and IHC results on the patient's LUAD tissue also suggest a possible functional role of BAP1 in this tumor, albeit at a later stage of tumor progression. Interestingly, we observed loss of BAP1 expression in the nucleus and in cytosol of meningioma cells as well as in BCC cells from two different germline BAP1 PV carriers belonging to two different families, confirming that meningioma and BCC are also included in the broader BAP1-TPDS spectrum [7,49,50].…”
Section: What Can We Say About the Tpds Spectrum?supporting
confidence: 70%
“…Of note, our NGS and IHC results on the patient's LUAD tissue also suggest a possible functional role of BAP1 in this tumor, albeit at a later stage of tumor progression. Interestingly, we observed loss of BAP1 expression in the nucleus and in cytosol of meningioma cells as well as in BCC cells from two different germline BAP1 PV carriers belonging to two different families, confirming that meningioma and BCC are also included in the broader BAP1-TPDS spectrum [7,49,50].…”
Section: What Can We Say About the Tpds Spectrum?supporting
confidence: 70%
“…BAP1 is a kind of deubiquitinase that regulates various cellular functions including proliferation, differentiation, and metabolism ( 77 , 78 ). BAP1 is mutated in lung cancer, thyroid cancer, kidney cancer, melanoma, and mesothelioma ( 79 81 ). Previous studies have found that the rate of BAP1 mutation increases with the increase in the ccRCC stage.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated SMARCE1 loss to be associated with reduced DNA accessibility over distal enhancer sites, and SMARCE1-deficient cells were susceptible to mSWI/ SNF inhibition [29]. Another rare alteration in aggressive meningiomas was inactivation of BAP1 [breast cancer (BRCA)1-associated protein-1 tumor suppressor] [30][31][32]. BAP1 loss on IHC was more common in histologically rhabdoid and papillary meningiomas (WHO grade 3), although more cases are being reported in exclusion of these histological subtypes [31].…”
Section: Non-nf2 Mutationsmentioning
confidence: 99%
“…Another rare alteration in aggressive meningiomas was inactivation of BAP1 [breast cancer (BRCA)1-associated protein-1 tumor suppressor] [30][31][32]. BAP1 loss on IHC was more common in histologically rhabdoid and papillary meningiomas (WHO grade 3), although more cases are being reported in exclusion of these histological subtypes [31]. Less than 30 cases have reported, including germline and somatic BAP1 mutations, and almost universally with poor outcomes.…”
Section: Non-nf2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation